Optimizing the role of health volunteers in early detection of non-communicable diseases through community nursing education - Hijrah Hijrah; Fransisca B. Batticaca; M.Khalid Fredy Saputra; Sarifudin Andi Latif (Edukasi Ilmiah Indonesia, 2025)
The rising prevalence of non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and cardiovascular conditions poses a significant public health challenge, particularly among the productive age population. Early detection is essential to prevent complications and reduce the disease burden. However, limited human resources in primary healthcare often hinder optimal screening efforts. This community service initiative aimed to optimize the role of health volunteers in the early detection of NCDs through community nursing education. The program included participatory training sessions covering educational modules, practical simulations of blood pressure and glucose monitoring, and the development of effective health communication skills. Post-training evaluations significantly improved the volunteers’ knowledge and competencies in conducting independent NCD screenings. The outcomes suggest that community-based educational interventions can empower health volunteers as frontline agents in promotive and preventive healthcare. This model holds promise for sustainable community engagement in NCD control strategies.